Winter Expansion and Emergence Time Effects on the Phenology, Growth, and Fecundity of Feathertop Rhodes Grass (Chloris virgata) - Alireza Hasanfard; Bhagirath Singh Chauhan (Agronomy)
Feathertop Rhodes grass (Chloris virgata Sw.) is a problematic weed in Australian summer crop fields that has recently expanded its presence into colder seasons. In this study, the phenology, growth, and seed production of four C. virgata populations were investigated across six different planting dates every other month from May to March between 2021 and 2022 and between 2022 and 2023. In both years, the shortest time (3 to 6 days) for C. virgata emergence was observed for January planting, while the longest time (10 to 17 days) was observed for July planting. In both years, C. virgata populations showed variations in growth and seed production in response to planting time. The highest aboveground biomass production in the first year was observed in November planting, and in the second year, it was observed in both November and January plantings. In the first year, all four populations produced the highest number of seeds when planted in January, averaging 133,000 seeds plant−1. In the second year, among the different planting dates, the March planting with two populations resulted in the highest seed production, averaging 148,000 seeds plant−1. In both years, there was a positive and significant correlation between aboveground biomass and seed production. The ability of this species to emerge, establish, survive, and consistently produce seeds year-round indicates its successful adaptation to the Queensland climate. Failure to manage this weed will result in its further spread to new areas.